(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
Ticks, the notorious ectoparasite, are frequently infest cattle and cause various disease conditions and acts as vector of pathogenic organism. To determine the tick infestation in cattle of four Districts of Rajshahi Division, Bangladesh, a total of 1200 cattle (300 from each district) were randomly examined throughout the year. Four hundred ticks (100 from each district) collected from cattle were microscopically identified to determine the prevalence of specific ticks. Among the examined cattle, 433 (36.08%) were found infested with one or more species of ticks. The highest prevalence was recorded in Naogaon District (39.66%) followed by Rajshahi (37.33%), Joypurhat (34.33%) and Natore (33%). Tick infestation rate was higher (p<0.05) in rainy season (43%) followed by summer (37.75%) and winter (27.5%). Adult cattle (>5 years) were significantly (p<0.05) susceptible (41.63%) to tick infestation in comparison to young (>1-<5 years) (29.94%) and calves (<1 year) (34.13%). Significant difference (p<0.05) was observed in sex related infestation. Female were highly susceptible (48.31%) than male (19.92%). Local breed cattle were significantly susceptible (41.97%) compare to North Bengal Gray (37.28%) and cross breed (26.60%) cattle. Ear was the most favorite (72.51%) infestation site of tick whereas least was found in scrotum (5.31%). Microscopic identification revealed 5 different species of ticks. Boophilus/ Rhipicephalus microplus was the most prevalent (33.5%) species followed by Haemaphysalis bispinosa (23.50%), Amblyomma variegatum (17.25%), Rhipicephalus sanguineus (14%) and Hyalomma anatolicum anatolicum (11.75%). Notable tick infestation in cattle indicated the possibility of damaged by ticks and opportunity of transmission of pathogenic organism. Thus, an effective control strategy is warned to overcome the harmful effects of ticks on cattle. Vol. 9, No. 2, August 2022: 171-183